GABAergic feedback signaling into the calyces of the mushroom bodies enables olfactory reversal learning in honey bees - Boitard, Constance; Devaud, Jean-Marc; Isabel, Guillaume; Giurfa, Martin (Frontiers in Behavioral Neuroscience, 2015)
In reversal learning, subjects first learn to respond to a reinforced stimulus A and not to a non-reinforced stimulus B (A+ vs. B-) and then have to learn the opposite when stimulus contingencies are reversed (A- vs. B+). This change in stimulus valence generates a transitory ambiguity at the level of stimulus outcome that needs to be overcome to solve the second discrimination. Honey bees (Apis mellifera) efficiently master reversal learning in the olfactory domain. The mushroom bodies (MBs), higher-order structures of the insect brain, are required to solve this task. Here we aimed at uncovering the neural circuits facilitating reversal learning in honey bees. We trained bees using the olfactory conditioning of the proboscis extension reflex (PER) coupled with localized pharmacological inhibition of GABAergic signaling in the MBs. We show that inhibition of ionotropic but not metabotropic GABAergic signaling into the MB calyces impairs reversal learning, but leaves intact the capacity to perform two consecutive elemental olfactory discriminations with ambiguity of stimulus valence. On the contrary, inhibition of ionotropic GABAergic signaling into the MB lobes had no effect on reversal learning. Our results are thus consistent with a specific requirement of the feedback neurons providing ionotropic GABAergic signaling from the MB lobes to the calyces for counteracting ambiguity of stimulus valence in reversal learning.